Sor Juana Inés de La Cruz : uma breve leitura das invocações e características de Maria - Silva, Eliane (2015)
The objective of this research is to identify and relate the various references and features of Mary in the work of Sor Juana Inés de la Cruz, from the more traditional theological aspects attributed to the Virgin. Born in San Miguel de Nepantla in 1651. At the age of nineteen she left the court's protection and opted to profess the Order of Jeronimas, where she produced most of her literary work in prose, verse, theater, novels, sonnets, love poetry, carols,letters, philosophical and theological writings. She wrote latin and castilian poems in the mexican language and in several dialects of the region. Maria clared to discuss and claim for the women of her time, the right to study and knowledge. Moreover, their knowledge in several areas of science were considered extraordinary for the occasion. She came to challenge in writing the Sermon of Mandate on the jesuit priest Antonio Vieira, with serious repercussions and ramifications at the time but whose discussion on the subject extends to the present day. From these initial observations, we examine how Sor Juana would have represented some notions of Mary's figure, especially in her carols in honor of the Conception and the Assumption of our lady and part of her prose writings, articulated how these notions in a particular type of narrative that sometimes tends to acquire a specific meaning. The intention is to analyze the relationships between these narratives and the context lived by religious woman in wich contex we understand as strongly shaped by the Christian faith, but also discussions, beliefs, theological challenges, literary and political. Therefore, this study intends to integrate different areas such as history, philosophy and the baroque literature of New Spain. From this research, we intend to contribute by bringing to the debate a topic and a time that are also part of the history of the Church and the religious and cultural thinking that permeated Mexico of XVII century, and adds a feminine name to the Scholastic Colonial Latin America.